Troubling texts in the New Testament essays in honour of Rob van Houwelingen - Houwelingen, P. H. R. van 1955-; Klinker-De Klerck, Myriam; Heijer, Arco den 1989-; Nes, Jermo van 1986- (Leuven Peeters, 2022)
Preface --Introduction /Myriam Klinker-De Klerck ; Arco den Heijer ; Jermo van Nes --Thunderbolt From the Open Sky: Jesus’ Claim on Revelation /Henk Bakker --A Troubling Instruction from Jesus in Matthew 23:3? /Francois Viljoen --An Uncomfortable Story from the New Testament: About Making Friends with the Mammon (Luke 16:1–13) /Bart J. Koet --Thinking Twice: Reconsidering the Johannine Presentation of the Temple Incident (John 2:13–15) /Roelof Alkema --Hapax Legomena in the Pericope Adulterae (John 7:53–8:11): A Linear Regression Analysis of Johannine Vocabulary /Jermo van Nes --Was John’s Jesus anti-Jewish and anti-Semitic? Fresh Perspectives on John 8:44 /Jacobus Kok --The Outpouring of the Spirit “On All People”: Acts 2:17–18 as Key to Explicating Inclusive Language /Erik A. de Boer --An Unbearable Yoke? The View of the Law in the Last Words of Peter in Acts (Acts 15:7–11) /Arco den Heijer -- Acts 23:27 and Acts 16:6: Two Problem Passages that Require Better Explanations /Stanley E. Porter --How to Inherit the Kingdom of God? First Corinthians 6:1–11 and Kenotic Suffering Through the Lens of Honour Discourse /Myriam Klinker-De Klerck --Unavoidable haireseis in the Church: 1 Corinthians 11:19 in Patristic Reception between 350 and 450 AD /Riemer Roukema --God’s Election of the ἐκκλησία in Ephesians 1:4 /Mark Grundeken --Gender Trouble in 1 Timothy 2:8–15 /Peter-Ben Smit --Saving Wealthy Ephesian Women from a Self-centerd Way of Life (1 Tim 2:15): Salvation by Childbearing in the Context of Ancient Arguments against Sexual Intercourse, Pregnancy, and Child-rearing /Armin Baum --Paul’s Plea to Philemon: The Societal and Rhetorical Context of an Unstated Request /Michael Mulder --“About to Disappear”: Hebrews 8:13 and the Destruction of the Temple /William den Hollander --“Through the Eternal Spirit” (Heb 9:14): The Arguments for and Implications of Interpreting the Phrase as a Reference to the Holy Spirit /Albert Coetsee --Imagery, Intratextuality and Sexual Impurity in Jude 22–23 /Riemer A. Faber --Coping with Revelation 2:20–23 /Jan Willem van Henten --Who can this be? Reconsidering the Rider on the White Horse (Revelation 6:2) /Pieter J. Lalleman --Death as the Ultimate Enemy of God and Creation: The Key to the Interpretation of the Four Horsemen in Revelation 6:1–8 /Pieter G.R. de Villiers --Identity Matters in the Book of Revelation: The Rhetorical Device of σύγκρισις as a Key to Its Structure and Message /Arie W. Zwiep --Indices --Tabula gratulatoria --Personalia – About the authors
Includes bibliographical references and indexes
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Houwelingen, P. H. R. van -- 1955-; Bible -- Criticism, interpretation, etc; Festschrift